Interspecies trophic niche differences and spatial–temporal adaptations found in Cultrinae fishes - Yang, Tingyue; Yang, Shufan; Yu, Dan; Wang, Chunling; Shang, Kunyu; Liu, Huanzhang (Frontiers in Ecology and Evolution, 2023)
It has been debated whether interspecies niche differences may follow niche conservatism, whether niches are becoming specialist, or generalist and specialist maintain in a balance, and how the realized niche may adapt to local or temporal environments. In the present study, by using stable isotope analysis to evaluate trophic niche of seven Cultrinae species, we investigated niche conservatism among these species from 10 sites of the Yangtze River by testing Mantel test of trophic niche variables (trophic position (TP), δ13C, trophic niche breadth). We also comprehensively investigated the fundamental niche differences as well as spatial and temporal adaptations of the realized niche of these seven Cultrinae species by calculating trophic niche breadths, overlap and TP. The results showed that, TP and fundamental trophic niche breadth exhibited phylogenetic conservatism, while fundamental trophic niche breadth of the three Hemicultrine species tended to become generalist and four Cultrine species tended to become specialist. Besides, the realized trophic niche of the same species would exhibit different adaptation at different sites as well as in different seasons. In wet season, trophic niche breadths of the seven species were significantly larger than that in dry season with great overlaps between species, while in the dry season, trophic niche separation were found among the seven species due to competitive exclusion of niches. We believe these findings will contribute to future theoretical and empirical niche investigations.